PENERAPAN MULTIMEDIA INTERAKTIF BERBASIS POWER POINT PADA PEMBELAJARAN MATEMATIKA KELAS IV SD NEGERI SIMPANG GEGAS TEMUAN TAHUN PELAJARAN 2021/2022 - Sari, Eka Aryunita; Mulyono, Dodik; Kusnanto, R. Angga Bagus (Jurnal Ilmiah Aquinas, 2022)
This study aims to determine the completeness of mathematics learning outcomes for grade IV students of elementary of school Simpang Gegas Temuan. After applying interactive multimedia based on power points. The research method used in this study was a quasi-experimental, with a one group pretest-postest design. The data collection technique in the form of an essay with a total of nine questions. The sample is grade four students, totaling 14 students. Data analysis technique with steps : calculating the average, and standard deviation, normality test and hypothesis testing. The result of the learning outcomes of grade IV students of elementary of school Simpang Gegas Temuan mathematics were significantly completed ofter the application of interactive multimedia based on power point. This in evident from the final test using the z test at a significant level = 0,05 ontained zcount (11,04) > ztable (1,64). So that is can be conclude that the learning outcomes of grade IV students of elementary of school Simpang Gegas Temuan are significantly completed after the application of interactive multimedia based on power points. Keywords : interactive multimedia based on power point